2006
DOI: 10.1038/sj.eye.6702459
|View full text |Cite
|
Sign up to set email alerts
|

The symptomatic Pulfrich phenomenon can be successfully managed with a coloured lens in front of the good eye—a long-term follow-up study

Abstract: Purpose Many visual symptoms originating from a spontaneous Pulfrich phenomenon can be alleviated by the provision of a tinted lens worn in front of the least affected eye. Here, we report on the long-term outcome of four patients who have been provided with a uniocular tinted spectacle or contact lens. Methods The case notes of four cases were reviewed. The review period was at least 5 years in all four cases. Results In all cases, visual symptoms and perceptual difficulties occurring from the spontaneous Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…For instance, it has been found that the Pulfrich effect appears to distort velocity and size besides giving an illusion of depth [39]. Evidence that these perturbations in judgment of spatial dimensions and motion can be problematic in a variety of situations ( Table 2) comes from a number of case reports and retrospective studies [22,23,32,36,[40][41][42]. Judging the distance of objects and people when they are moving with respect to the observer can be difficult, while problems also exist for judging height, width and depth.…”
Section: Motion-disparity Symptoms Associated With the Spontaneous Pumentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, it has been found that the Pulfrich effect appears to distort velocity and size besides giving an illusion of depth [39]. Evidence that these perturbations in judgment of spatial dimensions and motion can be problematic in a variety of situations ( Table 2) comes from a number of case reports and retrospective studies [22,23,32,36,[40][41][42]. Judging the distance of objects and people when they are moving with respect to the observer can be difficult, while problems also exist for judging height, width and depth.…”
Section: Motion-disparity Symptoms Associated With the Spontaneous Pumentioning
confidence: 99%
“…Problems with judging traffic impede driving [32], while being unable to judge motion accurately also affects performance in sports. Although some of these problems may seem mild, recognizing the symptoms of a spontaneous Pulfrich effect is important, as they may be potentially distressing and even dangerous, with the risk of road traffic accidents [36,43]. To investigate the influence of the Pulfrich effect on driving performance, Breyer et al [44] performed a three-dimensional computer driving simulation test on seven normal subjects, and found that the perturbation on vehicle position was greatest when the visual axis of the driver experiencing a Pulfrich effect was 90°to the direction of vehicle movement.…”
Section: Motion-disparity Symptoms Associated With the Spontaneous Pumentioning
confidence: 99%
See 2 more Smart Citations
“…The need to position displays like the TV and blackboard to give a normal visual perspective in the absence of an ocular motility or orthopaedic disorder is odd, and seems beyond the usual array of problems we have encountered in cases of spontaneous Pulfrich effect [20]. A recent paper [21] has investigated the Pulfrich effect provoked in normals, using a driving simulator.…”
Section: Discussionmentioning
confidence: 97%